The sonified boat motion as the characteristic rhythm of several stroke rate steps - Schaffert, N.; Mattes, K. (World Congress of Performance Analysis of Sport VIII, 2008)
The complex movement-acoustics information is a new approach to add to the technique analysis and rhythm education in racing boats and to describe the ideal boat run by the rhythm of the boat acceleration. The pilot study describes first-time acoustically the measured differences of the intensity between several stroke rate steps in the progress of acceleration for a coxless four. Typical differences of stroke rates during the boat acceleration regarding to the time structure, acceleration amounts as well as the positioning to the specific phases of a rowing cycle were verified and acoustically described. Comparable intensity differences were already described from Draper (2005) though for the single scull (1x). The modulation of the intensity differences resulted from pitch and sound volume. The rhythm of movement follows from the dependence to the time dimension. Now it exist a system which sonifies the acceleration-time-progress of the boat online as well as offline in the form of acoustic information (feedback and/or feedforward) and provides the information with chronological synchronism for or at on-water training. Following studies shall describe other characteristic race sections acoustically and try to sensitize the athletes to the rhythm of the sonified boat acceleration.